Pediatric advanced life support (PALS) and simulation - Takanari Ikeyama; Praveen Khilnani (Wolters Kluwer Medknow Publications, 2016)
Pediatric Advanced Life Support (PALS) course is a very popular course directed towards Pediatricians aimed towards improving the outcomes of sick children. However, despite the popularity of the course, translation of this knowledge to the bedside has been far from satisfactory due to variety of reasons. Few strategies have been employed to make the course more effective. Modular training by delivering PALS components in a staggered fashion over a defined time period, self-directed interactive web based learning, use of high fidelity simulators to deliver realistic scenarios, conducting the course in the provider's workplace using his resources and team and using reflective practice based debriefing technique to enhance learning from real life events have shown some promise.